(untitled) (Journal of Tikapur Multiple Campus, 2018)
This paper portrays on contemporary issues and discrepancies in Higher Education Institutions (HEIs) with References to Community Campuses of Nepal focusing on their existing governance system and legitimacy. Government need to have strong and explicit legislation to regulate almost all academic and administrative affairs of community campuses. This is essential ingredient to open the door for quality assurance of higher education system of Nepal. This study paper has taken into consideration these very aspects of community campuses. The specific objectives of the study were; to assess the existing governing system of community campuses and to identify issues and discrepancies of community campuses. This study is based on survey of selected community campuses of provinces seven and five of Federal Republic of Nepal. The main objective of this study is to explore the scope of existing governing system and identify the issues and discrepancies of community campuses of Nepal. There is found great variation and discrepancies in campus management committee formation process and its components, campus chief selection process and its tenure. Likewise, perception of teachers towards their career development was found to be gloomy. There is found substantial variation on workload of teacher and their recruitment process. The transparency and accountability, the hallmark of good governance are found to be poor amongst the respondent campus. The campuses have suffered a lot due to lack of financial sustainability. If this situation recurs for long in higher education arena, it would be catastrophic for nation as whole. Thus, existing scenario paves way to make inference that it is a high time for government and need to prepare strong legislation framework to regulate and address issues and discrepancies of overall governance of community campuses of Nepal.